Molecular epidemiology of Cryptosporidium spp. in dairy cattle in Guangdong Province, South China. Issue 1 (10th July 2018) - Liang, Nan; Wu, Yayun; Sun, Mingfei; Chang, Yankai; Lin, Xuhui; Yu, Linzeng; Hu, Suhui; Zhang, Xiangqian; Zheng, Shuangjian; Cui, Zhaohui; Zhang, Longxian
Abstract: To determine the prevalence of Cryptosporidium in dairy cattle in Guangdong Province, South China, 1440 fecal samples were collected from 10 farms and screened for Cryptosporidium with PCR. The overall prevalence of Cryptosporidium was 4.38% (63/1440), and the infection rates in preweaned calves, postweaned calves, heifers and adults were 6.4% (19/297), 6.19% (33/533), 1.48% (4/271) and 2.06% (7/339), respectively. Three Cryptosporidium species, Cryptosporidium andersoni ( n = 33), Cryptosporidium bovis ( n = 22) and Cryptosporidium ryanae ( n = 8) were detected by DNA sequence analysis of the 63 positive samples, and C. andersoni was identified as the most common species on the dairy cattle farms. In preweaned calves, C. bovis was the most prevalent species (9/19, 47.4%). In contrast, C. andersoni was the predominant species (19/33, 57.6%) in postweaned calves and the only species found in heifers and adults. The zoonotic species Cryptosporidium parvum was not detected in this study. Twenty-four C. andersoni isolates were successfully classified into three multilocus sequence typing (MLST) subtypes. MLST subtype A4, A4, A4, A1 was the predominant subtype, and MLST subtype A2, A5, A2, A1, previously found in sheep, was detected in cattle for the first time. A linkage disequilibrium analysis showed that the C. andersoni isolates had a clonal genetic population structure. However, further molecular studies are required to better understand the epidemiology of Cryptosporidium in Guangdong.